2013
DOI: 10.1063/1.4790379
|View full text |Cite
|
Sign up to set email alerts
|

The increase in conductance of a gold single atom chain during elastic elongation

Abstract: The conductance of monoatomic gold wires has been studied using ab initio calculations and the transmission was found to vary with the elastic strain. Counter-intuitively, the conductance was found to increase for the initial stages of the elongation, where the structure has a zigzag shape and the bond angles increase from %140 toward %160. After a certain elongation limit, where the angles are relatively high, the bond length elongation associated with a Peierls distortion reverses this trend and the conducta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 44 publications
3
16
0
Order By: Relevance
“…In such a scenario, the conductance is expected to decrease as the chain is stretched due to larger interatomic distances which reduce the interatomic coupling 35,37 and to increase following structural relaxation once an additional atom is pulled into the chain. However, the relative positions of the observed oscillations with respect to the peaks in the length histogram (Fig.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…In such a scenario, the conductance is expected to decrease as the chain is stretched due to larger interatomic distances which reduce the interatomic coupling 35,37 and to increase following structural relaxation once an additional atom is pulled into the chain. However, the relative positions of the observed oscillations with respect to the peaks in the length histogram (Fig.…”
Section: Main Textmentioning
confidence: 99%
“…As a result, atoms can be pulled out from the electrodes during the stretching process and a suspended chain of several atoms is formed between the two wire segments. First principles calculations suggest that such pulling experiments involve repeated transitions between zigzag 32 and linear atomic configurations as the chain is elongated [33][34][35] , illustrated schematically in Fig. 1a.…”
Section: Main Textmentioning
confidence: 99%
“…An oscillatory dependence of the conductance with the length of gold atomic chains has been reported by Smit et al [2], suggesting a dependence on whether the number of atoms in the chain is even or odd and originating from interference effects in the electron wave functions. However, Vardimon et al [3], carried out conductance and shot noise measurements, and inferred, consistent with theory [9], that the conductance oscillations of gold atomic chains during stretching are mainly related to variations in bond angles (and hence in orbital overlaps) as the chain undergoes transitions between zigzag and linear atomic configurations.…”
Section: Introductionmentioning
confidence: 69%
“…In the past two decades, the formation, evolution, and breaking of gold atomic chains that bridge a pair of electrodes have been the subject of many experimental and theoretical studies, motivated by their fundamental scientific interest and potential applications as the narrowest possible conducting wires for nanoscale electronic devices [1][2][3][4][5][6][7][8][9][10]. The electric current through such atomic chains can be measured in scanning tunneling microscopy experiments [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…65 Conductance across MCBJs as tunneling electron microscopy images are taken shows that as multiple atoms are individually added to the chain, the conductance oscillates in a consistent manner. 60,[66][67][68][69] Careful studies of similar chains occurring when a molecule is present in the junction have shown that metal chains of four atoms long can occur before the junction breaks. 70 Other simulation work has shown the effects of slipping gold-gold bonds ( Figure 3B and C) and molecule-electrode slipping (Figure 3D and E) and twisting ( Figure 3F and G) on conductance in MCBJs.…”
Section: Importance Of Contact Geometry and Evolution In Mcbjsmentioning
confidence: 99%